NEW BRANDING TECHNOLOGIES THAT TRIGGER BRAND ENGAGEMENT. BRANDING PRACTICES IN THE FMCG MARKET IN RUSSIA - S. Samoylenko, Irina; Y. Ladogina, Anastasia; Golovina, Vera V.; A. Razina, Natalia; Petushkova, Elena (Revista Inclusiones, 2021)
The article examines one of the innovative technologies for branding FMCG goods as one of the techniques of value emotation. The relevance of the study is due to the high level of competition in the segment and the complexity of brand differentiation both at the functional and rational level, and at the emotional level. The impulse emotional response to the brand's product, which is of particular importance in the segment, is becoming more difficult and standard branding techniques do not always succeed. This article provides an analysis of the cases of the leaders of the FMCG market and agencies, the profile of which is the development of visual brand communication in order to identify technologies that can solve the problem of emotional brand differentiation in the most effective way. The results of the study show that the most promising is the storytelling technology in branding, which carries out a targeted impact on the consumer if the storytelling is omnichannel - telling a story both verbally and visually.